A Short‐term Study to Compare Field Strategies for Ammonia Emission Mitigation. Issue 1 (1st January 2019) - Yagüe, María R.; Valdez, Alcira S.; Bosch‐Serra, Àngela D.; Ortiz, Carlos; Castellví, Francesc
Abstract : Abatement of NH3 emissions is crucial in calcareous soils under semiarid Mediterranean climates. The aim of the study was to compare NH3 emissions using different slurry application methods. An experiment was performed on a clay loam soil to evaluate NH3 emissions before sowing and at winter cereal tillering. Pig slurry was applied using two methods, one that applied slurry by splashing it over a plate (SP), and another that applied slurry in strips using trail hoses (TH). Emissions were measured using semi‐static chambers at variable intervals for 12 to 13 d (315.5 h for sowing and 287 h for tillering). Maximum NH3 flux emissions were always observed during the earliest period of measurements after slurry spreading (3.5–5 h). Before sowing, regardless of the method, accumulated NH3 losses (during 315.5 h) ranged between 2 and 3 kg NH3 –N ha −1 because of the low dry matter content of the slurry (<2%), which enhanced infiltration. Losses represented about 2 to 3% of the total N applied. At cereal tillering, average accumulated losses of NH3 (during 287 h) were 1.7 kg N ha −1 using TH (1.1% of total N applied) and were as high as 5.4 kg N ha −1 (3.2% of total N applied) using SP. Because N topdressing is recommended as a measure to increase its efficiency, TH is recommended over SP. Thus, this short‐term study concludes that TH may reduce NH3 emissions in semiarid environments. Further study of these strategies is recommended under different climate and soil conditions. Core Ideas: NH3 emissions from slurry splash plate (SP) spreading can be <4% of the NH4 + applied. Trail hoses (TH) reduce NH3 emissions from slurries versus SP at cereal tillering. At sowing, low slurry dry matter bridges the gap in NH3 emissions between TH and SP.